Effect of Tapper Ratio on a Car Rear Spoiler Performance - Harianto Harianto; Yosua Heru Irawan; Eka Yawara; Husni Bakhtiar (University of Muhammadiyah Malang, 2019)
The increasing development of car modification and the lack of understanding on the function of using spoilers or rear wings on vehicles, underlies the research on the aerodynamic forces acting on cars. The influence of this aerodynamic device will produce a compressive force to the bottom of the vehicle or called downforce, where this force is greatly influenced by the CL (lift coefficient) value. The purpose of this study was to determine the effect of variations in the tapper ratio on the value of downforce and drag force on on single-element type spoilers made using a NACA 6412 airfoil. The research was conducted using the Computational Fluid Dynamic method using ANSYS Fluent software with steady state pressure based solver. In this study five variations of the tapper ratio were used, namely: 1:1; 1:0.5; 1:0.7; 0.5:1; and 0.7:1. The fluid properties used are adjusted to the climate and weather in general air conditions and at air flow speeds of 100 km/h. Based on the research conducted, it can be concluded that the highest lift coefficient value was achieved in the 1:1 tapper ratio variation which was equal to CL = -0.2275 and CD = 0.0195. The highest downforce value is achieved in the 1:1 tapper ratio variation that is equal to L = -107,529 N and the largest drag force value is also achieved in the 1: 1 tapper ratio variation that is equal to D = 9.2269 N. The best CL/CD results are obtained at the 1:05 tapper ratio variation with a value of 12.82.